2003
DOI: 10.1093/icb/43.2.305
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Receptors and Signal Transduction in Molluscan Hemocytes: Connections with the Innate Immune System of Vertebrates

Abstract: The involvement of circulating hemocytes as the principal cellular effector mediating molluscan immune responses is well established. They participate in a variety of internal defense-related activities including microbial phagocytosis, multicellular encapsulation, and cell-mediated cytotoxicity reactions that are presumed to be initiated through foreign ligand binding to hemocyte receptors and subsequent transduction of the binding signal through the cell resulting in appropriate (or in some cases, inappropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 69 publications
(73 reference statements)
1
29
0
Order By: Relevance
“…Parasite components such as ESPs play an important role in suppressing snail host immune defence mechanisms, mainly by interfering with the physiology and behaviour of host haemocytes (reviewed by Humphries and Yoshino 2003). Our previous study showed that S. mansoni ESPs are capable of attenuating ERK signalling in susceptible snail haemocytes (Zahoor et al 2008); in the current study, we have found that the inhibition of the ERK pathway also influences HSP70 protein levels in these cells.…”
Section: Hsp70 Protein Reduction May Be Regulated By Effects Of Esps supporting
confidence: 52%
“…Parasite components such as ESPs play an important role in suppressing snail host immune defence mechanisms, mainly by interfering with the physiology and behaviour of host haemocytes (reviewed by Humphries and Yoshino 2003). Our previous study showed that S. mansoni ESPs are capable of attenuating ERK signalling in susceptible snail haemocytes (Zahoor et al 2008); in the current study, we have found that the inhibition of the ERK pathway also influences HSP70 protein levels in these cells.…”
Section: Hsp70 Protein Reduction May Be Regulated By Effects Of Esps supporting
confidence: 52%
“…By histology, sporocysts near the radula were found. According to Humphries & Yoshino (2003), the elimination of metazoan parasites, such as trematodes, by molluscs would be directly associated with the formation of multicellular capsules of haemocytes, in a coordinated action with soluble factors of the haemolymph. In the Biomphalaria spp.…”
Section: Discussionmentioning
confidence: 99%
“…If attention is focused on the functional attributes of hemocytes, several reports in this direction revealed diverse immunological functions such as phagocytosis [34], cytotoxicity [35], aggregation [36] and pathogen encapsulation [37,38]. In addition to hemocytes, hemolymph, the humoral component of the molluscan immune system, is reported to exhibit the activities of superoxide dismutase [39], catalase [40] and acid [41] and alkaline phosphatases [42].…”
Section: Role Of Snail Hemocytes In Innate Immunitymentioning
confidence: 99%
“…Acid and alkaline phosphatases are functionally involved in pathogen destruction in phagolysosome which bear immunological significance [50]. Several reports also demonstrated a range of receptors which bind carbohydrates, extracellular matrix proteins, hormones, growth factors and cytokines resulting specific immunocyte signals not only in vertebrates but also in molluscs [37]. Thus, it can be surmised that signaling systems are evolutionary conserved functions of immunocytes in the animal kingdom.…”
Section: Role Of Snail Hemocytes In Innate Immunitymentioning
confidence: 99%